Comparison of The Macroeconomic Effects of The Processes of Fighting the COVID-19 Pandemic in Sweden and Poland - Jagoda WLODARSKA; Jacek WINIARSKI (Communications of International Proceedings, 2022)
The aim of the article is to present a comparison of economic and social conditions between Sweden and Poland during the COVID-19 pandemic (from March 2020 to December 2021). The first part of the text presents an analysis of selected economic aspects of the course of the pandemic in Sweden and Poland and characterizes the actions of governments initiated to reduce the effects of economic recession. Then, a comparative study of fluctuations in selected macroeconomic data is presented, and the dynamics of economic change is determined based on these data. Measures such as GDP, labour demand, unemployment rate and corporate bankruptcy are analysed. The study of these measures makes it possible to present comparisons of fluctuations taking place on the labour market in Sweden and Poland. Based on the analyses of the magnitudes of the examined measures, a synthetic assessment is made of the effectiveness of the implemented government programmed aimed at supporting the functioning of the Polish and Swedish economies during the COVID-19 pandemic during the examined period. A comparison of the fight against the pandemic using Sweden and Poland as an example is a research gap since there are no studies comparing the two countries in terms of their methods of supporting economic processes in a crisis caused by the SARS-CoV-2 coronavirus.
Keywords: Crisis management; COVID-19 pandemic; Macroeconomics